Pandangan Hak Asasi Manusia (HAM) Islam Terhadap Convention On The Elimination Of All Forms Of Discrimination Against Women (CEDAW) (Studi Kritis Pasal 5 Tentang Kesetaraan Perempuan) - Jannah, Miftahul; , Dr. Sudarno Shobron, M.Ag; , Dr. Aidul Fitriciada Azhari, SH., M.Hum (2015)
Gender equality issues lately has become a contemporary issue and continue to cause controversy, in term of in the world of Islamic thought. It is influences in life and used as a social program designed academically. The guide feminists have binding legal force is the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). correspondence in Article 5 of the convention which is in the future could be the object of this research using human rights as a subject of Islam. This instrument has international standard was adopted by the United Nations in 1979. The Convention which began since on 3 December 1981 establishes universal principles of equality between men and women and is recognized by the world as the inscription of Women's Rights (Bill of Rights of Women). The purpose of this research was to determine the perspective of the Islamic Human Rights according to women's equality in Article 5 of CEDAW. By this research could be said is library research that using a philosophical approach. The primary data is the draft CEDAW in 1981. In addition, for the secondary data material in the form of books, articles, papers and journals related to the research theme that the equality of women in CEDAW and Human Rights (HAM) Islam. Before performing the analysis in the mentioned prior history, principles and scope of the Islamic Human Rights, CEDAW history and content of Article 5 of CEDAW which is seen from general recommendations, reports, and final comments on the implementation of the convention and then the deductive method, analyzed by dotted and based on rules of a general nature, then be concluded a particular conclusion through this method is expected to conclude the Islamic Human Rights views the concept of equality in article 5 of CEDAW. Based on the results of the research conducted, there are some things that referred to in Article 5 of CEDAW, that is the obligation for each country to eliminate discriminatory attitudes or behavior, it is more focused on the private sphere is the family, including the family's leadership, the concept of family, hadhanah (childcare) and discrimination in cultural and social as well, everything about this considered to violate the rights of women and discriminate. Moreover, to make the strengthening of these research analysis, the authors used a particular point of view relative to see CEDAW. Hence, that in the implementation still taking pay attention the diversity of cultural, historical and religious backgrounds in each territory. Islamic human rights is loaded with Islamic law has a different perspective to what is desired by the CEDAW. So that in the analysis of some elements described in the draft feminists who dominate the CEDAW so appropriate that some of the articles of CEDAW contrary to Islamic law.